1993
DOI: 10.1073/pnas.90.6.2137
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of long DNA: imaging in air and under water.

Abstract: We have obtained striking atomic force microscopy images of the intact A bacteriophage genome and of several A restriction fragments both in air and under water. The DNA is unstained and the images are stable under continuous scanning for up to 30 min. Measured contour lengths of fully imaged restriction fragments and intact A DNA are accurate to within a few percent. The key to this development is the use of a process for binding unmodified double-stranded DNA to chemically treated mica surfaces. This procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(173 citation statements)
references
References 12 publications
2
169
0
2
Order By: Relevance
“…The AP-mica has speci®c surface characteristics that should be considered in understanding the behavior of DNA molecules and the cruciforms in particular at the surface-liquid interface and their interaction with the surface. As discussed in our previous publications (Lyubchenko et al, 1992(Lyubchenko et al, , 1993b(Lyubchenko et al, , 1995Lyubchenko & Shlyakhtenko, 1997), AP-mica is a positively charged surface with uniform and comparatively low surface charge density. There are three main consequences of these characteristics of AP-mica.…”
Section: Structure Of Cruciformsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AP-mica has speci®c surface characteristics that should be considered in understanding the behavior of DNA molecules and the cruciforms in particular at the surface-liquid interface and their interaction with the surface. As discussed in our previous publications (Lyubchenko et al, 1992(Lyubchenko et al, , 1993b(Lyubchenko et al, , 1995Lyubchenko & Shlyakhtenko, 1997), AP-mica is a positively charged surface with uniform and comparatively low surface charge density. There are three main consequences of these characteristics of AP-mica.…”
Section: Structure Of Cruciformsmentioning
confidence: 99%
“…The key in the AFM sample preparation procedure is the use of the functionalized substrate (AP-mica) which permits one to obtain high resolution AFM images of DNA by a one step deposition from a very wide range of ionic conditions (Lyubchenko et al, 1992(Lyubchenko et al, , 1993aLyubchenko & Shlyakhtenko, 1997). This procedure is highly reproducible and allows one to perform imaging in air or in aqueous solutions (Lyubchenko et al, 1992(Lyubchenko et al, , 1993bLyubchenko & Shlyakhtenko, 1997).…”
Section: Afm Imaging Of Cruciforms In Supercoiled Dnamentioning
confidence: 99%
“…The precise nature of the DNA-surface interactions is still unclear so we set out to compare three different methods: (i) AP-mica (14); (ii) nickel-treated mica (15); and (iii) mica treated with Mg alone (18) without the use of HEPES (17). We found that the magnesium treatment causes linear DNA to condense on the surface (an effect not observed with small circles; 18).…”
Section: Resultsmentioning
confidence: 99%
“…Several different approaches to binding DNA for imaging under buffer have been described in the literature (14)(15)(16)(17)(18). The precise nature of the DNA-surface interactions is still unclear so we set out to compare three different methods: (i) AP-mica (14); (ii) nickel-treated mica (15); and (iii) mica treated with Mg alone (18) without the use of HEPES (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation